Pengelolaan Adiksi Game Online dalam Pembelajaran Keterampilan Komputer dan Pengelolaan Informasi pada Siswa SMK - Nurul Hidayah; S. Sutama; Sabar Narimo (Manajemen Pendidikan, 2017)
This research aims to: (1) to describe the online game addiction managementplanning in KKPI learning at SMK Muhammadiyah 6 Gemolong, (2) to describethe implementation of online game addiction management in KKPI learningat SMK Muhammadiyah 6 Gemolong, (3) to describe evaluation from the onlinegame addiction management at SMK Muhammadiyah 6 Gemolong. The researchwas conducted with a kind of qualitative research with ethnographic approachdesign. With tkeknik data collection is in-depth interviews, documentation andobservation. Data analysis use an interactive analysis model. The results of thisstudy are; (1) online game addiction management planning with identification oflearners, searching for appropriate learning game reference, making lesson plansand evaluation instruments; (2) implementation of online game addiction in learningKKPI in accordance with the planning that has been made and implemented to adjustthe current situation; and (3) evaluation of online game addiction in KKPI learningdone during daily test, mid semester test and final semester test.